Between Past and Future - 1/20
Recording of the Q&A session with the audience of the fourth panel entitled “Vulnerabilities of the New Democracies.” The members of he panel are Katherine Verdery (Professor at the University of Michigan), Gail Kligman (University of California Los Angeles), Kazimierz Poznanski (Professor at the University of Washington), István Rév (Professor at CEU and Director of OSA Archivum) and Miklós Haraszti (Hungarian Writer, Journalist and Professor) who are among the key participants of the “Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" international conference held at CEU in March 1999. After the debate, U.S. Congressman Tom Lantos shares his thoughts on the issue of civility and consensus building in institutions of representational democracy. The fifth and closing panel that followed the next day was entitled "The New Europe: Prospects for Cooperation and Conflict” and was chaired by CEU Professor Alfred Rieber. The speakers are Karen Dawisha (Professor of Political Science at Miami University), Bartlomiej Kaminski (Associate Professor of Government at the University of Maryland), Ivo Banac (Croatian Historian and Politician), Ilya Prizel (Professor at John Hopkins University), Jeffrey Wasserstrom (Professor of History at the University of California), Irena Grudzińska Gross (Polish Historian and Professor) and Chairman Alfred Rieber. Prof. Alfred Rieber presents the speakers and Prof. Karen Dawisha delivers the first speech of the final panel.